Cytotoxic effects of organotin (IV) dithiocarbamate compounds with different functional groups on leukemic cell line, K-562 - Asmah Hamid,; Mohd Azam Azmi,; Nor Fadilah Rajab,; Normah Awang,; Nurul Farhana Jufri, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Cancer is one of the main causes of mortality in the world. New compounds are currently being synthesized to overcome this disease. Organotin is getting more attention as anticancer agent due to its potent cytotoxic properties towards cancer cells. In this study, a series of newly synthesized organotin compounds known as dimethyltin(IV) (compound 1), dibutyltin(IV) (compound 2) and triphenyltin(IV)methylisoprophyldithiocarbamate (compound 3) have been assessed for their cytotoxic effect towards leukemic cell line K-562. MTT [3-(4,5-dimethylthiozol-2-yl)-2,5-diphenyltetrazolium bromide] assay was employed to determine the cytotoxic effect for each of the compounds at different time points and concentrations. Compound 2 and 3 exhibited potent cytotoxic effects towards K-562 cells with IC50 values less than 2 µM. Compound 3 was found as the most toxic towards K-562 cells based on the lowest IC50 value for 72 h period of treatment at 0.25 µM. Morphological observation was conducted with IC50 values at 24, 48, and 72 h. Results showed that the changes were first observed as early as 24 h and the most significant changes were observed after 72 h period of treatment with the characteristic of apoptosis such as cell shrinkage and membrane blebbing. In addition, necrosis characteristic such as cell lysis and swelling had also been observed. Organotin(IV) methylisopropyldithiocarbamate with different functional groups affect the cytotoxic properties towards leukemic cells K-562 and these compounds have potential to be developed as an anticancer agent through structural modification.